+0  
 
0
350
1
avatar+88 

Given the function f(x)= x+1/x-3 Find the inverse of f(x). (use parenthesis to type your answer)

zandaleebailey  Mar 4, 2015

Best Answer 

 #1
avatar+80866 
+10

We want to get x by itself.......so we have

y = (x + 1) / (x - 3)   multiply both sides by x -3

y(x - 3)  = x + 1       simplify

yx - 3y = x + 1

yx - x = 1 + 3y

x(y - 1) = 1 + 3y

x =  (1 + 3y) / (y - 1)     "exchange" x and y

y = (1 + 3x) / (x - 1)   for "y," write f-1(x)

f-1(x) = (1 + 3x) / (x - 1)

Here's the graph of f(x) and f-1(x).....

https://www.desmos.com/calculator/t7vncorptl

 

CPhill  Mar 4, 2015
Sort: 

1+0 Answers

 #1
avatar+80866 
+10
Best Answer

We want to get x by itself.......so we have

y = (x + 1) / (x - 3)   multiply both sides by x -3

y(x - 3)  = x + 1       simplify

yx - 3y = x + 1

yx - x = 1 + 3y

x(y - 1) = 1 + 3y

x =  (1 + 3y) / (y - 1)     "exchange" x and y

y = (1 + 3x) / (x - 1)   for "y," write f-1(x)

f-1(x) = (1 + 3x) / (x - 1)

Here's the graph of f(x) and f-1(x).....

https://www.desmos.com/calculator/t7vncorptl

 

CPhill  Mar 4, 2015

5 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details